Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian : Studi Kasus Pada Tahu Bakso Khanza Lana Semarang Timur - Soegihartono Soegihartono (AKUNTANSI 45, 2022)
This study aims to study, analyze, and explain the influence of product quality, price, and promotion on simultaneous and partial purchasing decisions, as well as find out which independent variables have a dominant influence on the dependent variable. The sample in this study is consumers who purchase KL Meatball Tofu and are at least 20 years old. The research method used in this study was a quantitative research method using a sample of 96 respondents. Sampling using non-probability sampling with purpossive sampling techniques. The data analysis methods used in this study are descriptive analysis methods and multiple linear regression analysis. The results showed that simultaneously Product Quality, Price, and Promotion had a partial influence on purchasing decisions. This is shown by the results of multiple linear analysis Y = 0.298 X1 + 0.268 X2 + 0.242 X3 + e. The hypothesis test shows the results of the significance test t, the Price variable has the most significant influence on purchasing decisions. The results of the coefficient of determination test (adjusted r square) showed a value of 0.395 which means that the research variable was able to influence the purchase decision by 39.5%.